Growth and mineral nutrition Of Ipomoea quamoclit - Carvalho,L.B. (2009)
A greenhouse experiment was carried out from November 2006 to April 2007 at FCAV/UNESP, Brazil, aiming to study the dry mass production and the accumulation and distribution of macronutrients in Ipomoea quamoclit, an important weed for annual and perennial crops in Brazil. The plants were grown in seven liter pots with sand substrate, daily irrigated with Hoagland & Arnon nutrient solution. The experimental design was completely randomized with four replicates. The treatments corresponded to evaluation times at 14 day intervals, beginning 21 days after emergence (DAE). In each evaluation, the plants of four pots were analyzed in function of dry mass production and macronutrient content. I. quamoclit had a small dry mass and macronutrient accumulation at the beginning of the experimental stage, increasing after 77 DAE and reaching the maximum theoretical value at 146, 143, 140, 149, 142, 153, and 124 DAE, for dry mass, N, P, K, Ca, Mg, and S, respectively. K and N were the macronutrients most accumulated by I. quamoclit plants.